Functional metagenomic exploration identifies novel prokaryotic copper resistance genes from the soil microbiome. Issue 3 (16th January 2020) - Xing, Chao; Chen, Jinghao; Zheng, Xin; Chen, Liang; Chen, Miaomiao; Wang, Likun; Li, Xiaofang
Abstract : Functional metagenomics is a premise-free approach for exploring metal resistance genes, enabling more profound effects on the development of bioremediation tools than pure culture based selection. Abstract : Functional metagenomics is a premise-free approach for exploring metal resistance genes, enabling more profound effects on the development of bioremediation tools than pure culture based selection. Six soil metagenomic libraries were screened for copper (Cu) resistance genes in the current study through conventional functional genomics. Clones from the six metagenomic libraries were randomly selected from solid medium supplied with Cu, resulting in 411 Cu resistance clones. Thirty-five clones with the strongest Cu resistance were sequenced and 12 unique sequences harboring 25 putative open reading frames were obtained. It is inferred by bioinformatic analysis that putative genes carried by these recombinant plasmids probably function in the pathways of responding to Cu stress, including energy metabolism, integral components of membrane, ion transport/chelation, protein/amino acid metabolism, carbohydrate/fatty acid metabolism, signal transduction and DNA binding. The sequenced clones were re-transformed into Escherichia coli strain DH5α, and the host's biomass and the metal sorption under Cu stress were subsequently determined. The results showed that the biomass of eight of the clones was significantly increased, whereas four of them were significantly reduced. A negative correlation ( R = 0.86) was found between the biomass and Cu sorption capacity. The 12 positive clones were further transferred into a Cu-sensitive E. coli strain (Δ CopA ), among which nine restored the host's Cu resistance substantially. The Cu resistant genes explored in this study by functional metagenomics possess a potential capacity for developing novel bioremediation strategies, and the findings imply a vast diversity of microbial Cu resistance genetic factors in soil yet to be discovered.